ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN BERPIKIR KOMPUTASI PADA SISWA SMP : SYSTEMATIC LITERATURE REVIEW: Analysis Of Mathematical Problem Solving Ability Using Computational Thinking In Junior High School Students : Systematic Literature Review - Ghifari, Muhammad Al; Yahfizham, Yahfizham (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
Abstrak The computational thinking abilities of junior high school students are in the category of not meeting the criteria, many of the students make mistakes in finding mathematical solutions. This study will focus on problem solving abilities using computational thinking in junior high school students. The method used in this research is Systematic Literature Review (SLR) . This research method was carried out by analyzing, researching, assessing, cross-checking and interpreting all existing research results. The researcher categorized the computational thinking level of junior high school students from the articles referred to, namely high, medium and low level thinking. The research results from the 5 articles sampled show that junior high school computing thinking abilities are in the middle or categorized as moderate